Using Diaper Waste to Prepare Magnetic Catalyst for the Synthesis of Glycerol Carbonate - Jincan Wang; Yong Liang; Song Wang; Patrick U. Okoye; Hongxu Chen; Yue Zhou; Jiening Xu; Zhenhao Meng; Lei Wang; Sanxi Li (International Journal of Polymer Science)
Diaper waste was calcined above 400°C after impregnated in the solution of nickel nitrate. The as-prepared diaper waste-derived materials were used as magnetic catalysts for the synthesis of glycerol carbonate (GC). Structure and catalytic ability investigations on the catalysts calcined at different temperatures indicated that calcination temperature was an important factor affecting the property of catalysts. It was found that the catalyst obtained at the calcination temperature of 700°C (named DW-Ni-700) showed the best performance. When DW-Ni-700 was used in the synthesis of GC, GC yield reached 93.2%, and the magnetic property of DW-Ni-700 facilitated the catalyst separation process. Meanwhile, DW-Ni-700 showed high reusability in the reaction. After four times reuse of DW-Ni-700, GC yield decreased less than 4%.